SIGNIFYING RELIGION IN SYMBOL: LOOKING UP THE RISE OF INDONESIAN RED CRESCENT (BSMI) IN PUBLIC LIFE - Ahmad Yunus; Taufiqurrohim Taufiqurrohim (INJECT (Interdisciplinary Journal of Communication), 2019)
In the beginning, the surface of BSMI problematizes the red symbol that was used by PMI because it was analyzed as a Christian symbol, feeling hesitant when used as a cross symbol in humanitarian missions is the basic reason as their appearance of religiosities in public life. Talking about the symbol, the crescent has a long history of how it can be “identified” as a symbol of Islam and how the people identified those as an identity of the religion by signifying sacred behind the symbol. The symbolization of religion cannot be separated from the method of semiotic approach where explains the science of sign. Through this sign, people can find their identity and communicatewith each other as social interaction and also find a sacred behind the symbol. For the last theory, I would use the social movement and development that indicate the turn organization not only happen in the case of philanthropy but also will eradicate to the other social application movement. Therefore, in my opinion, the surface of BSMI cannot be rid by the development of crescent symbol interpretation as a symbolization of religious identity due to symbolism as a way to communicate and interact with society